Reducing inappropriate psychotropic drug use in nursing home residents with dementia: protocol for participatory action research in a stepped-wedge cluster randomized trial - Claudia M. Groot Kormelinck (BMC Psychiatry, 2019)
Abstract Background Psychotropic drugs are often prescribed to treat neuropsychiatric symptoms in nursing home residents with dementia, despite having limited efficacy and considerable side effects. To reduce the inappropriate prescribing of these psychotropic drugs, various non-pharmacological, psychosocial, person-centered, or multidisciplinary interventions are advocated. However, existing multidisciplinary interventions have shown variable effects, with limited effectiveness often resulting from suboptimal implementation. We hypothesize that an effective intervention needs to fit the local situation of a nursing home and that support should be offered during implementation. Methods We will embed participatory action research within a stepped-wedge cluster randomized controlled trial to study the effects of a tailored intervention and implementation plan to reduce inappropriate psychotropic drug prescribing. Nursing homes will be provided with tailored information about the perceived problems of managing neuropsychiatric symptoms and we will offer coaching support throughout. Alongside the participatory action research, we will perform a process evaluation to examine the quality of the study, the intervention, and the implementation. Our aim is to recruit 600 residents from 16 nursing homes throughout the Netherlands, with measurements taken at baseline, 8 months, and 16 months. Nursing homes will be randomly allocated to an intervention or a deferred intervention group. During each intervention stage, we will provide information about inappropriate psychotropic drug prescribing, neuropsychiatric symptoms, and difficulties in managing neuropsychiatric symptoms through collaboration with each nursing home. After this, a tailored intervention and implementation plan will be written and implemented, guided by a coach. The primary outcome will be the reduction of inappropriate prescribing, as measured by the Appropriate Psychotropic drug use In Dementia index. Secondary outcomes will be the frequency of psychotropic drug use and neuropsychiatric symptoms, plus quality of life. A mixed methods design will be used for the process evaluation. Effects will be assessed using multilevel analyses. The project leader of the nursing home and the coach will complete questionnaires and in-depth interviews. Discussion We anticipate that the proposed tailored intervention with coaching will reduce inappropriate psychotropic drug prescribing for nursing home residents with neuropsychiatric symptoms. This study should also provide insights into the barriers to, and facilitators of, implementation. Trial registration NTR5872, registered on July 2, 2016.